Comparison of the prognostic performance of the CURB-65 and a modified version of the pneumonia severity index designed to identify high-risk patients using the International Community-Acquired Pneumonia Collaboration Cohort. (August 2022) - Barlas, Raphae S.; Clark, Allan B.; Loke, Yoon K.; Kwok, Chun Shing; Angus, Derek C.; Uranga, Ane; España, Pedro P.; Eurich, Dean T.; Huang, David T.; Man, Shin Y.; Rainer, Timothy H.; Yealy, Donald M.; et al.
Abstract: Background: Although the PSI and CURB-65 represent well-validated prediction rules for pneumonia prognosis, PSI was designed to identify patients at low risk and CURB- 65 patients at high risk of mortality. We compared the prognostic performance of a modified version of the PSI designed to identify high-risk patients (i.e., PSI-HR) to CURB-65 in predicting short-term mortality. Methods: Using data from 6 pneumonia cohorts, we designed PSI-HR as a 6-class prediction rule using the original prognostic weights of all PSI variables and modifying the risk score thresholds to define risk classes. We calculated the proportion of low-risk and high-risk patients using CURB-65 and PSI-HR and 30-day mortality in these subgroups. We compared the rules' sensitivity, specificity, positive and negative predictive values for mortality at all risk class thresholds and assessed discriminatory power using areas under their receiver operating characteristic curves (AUROCs). Results: Among 13, 874 patients with pneumonia, 1, 036 (7.5%) died. For PSI-HR versus CURB-65, aggregate mortality was lower in low-risk patients (1.6% vs. 2.2%, p = 0.005) and higher in high-risk patients (36.5% vs. 32.2%, p = 0.27). PSI-HR had higher sensitivities than CURB-65 at all thresholds; PSI-HR also had higher specificities at the 3 lowest thresholds and specificities within 0.5% points of CURB-65 at the 2 highest thresholds. The AUROC was larger for PSI-HR than CURB- 65 (0.82 vs. 0.77, p < 0.0001). Conclusions: PSI-HR demonstrated superior prognostic accuracy to CURB-65 at the lower end of the severity spectrum and identified high-risk patients with nonsignificant higher short-term mortality at the higher end. Highlights: Clinical Significance. PSI-HR identified a larger number of low-risk patients with a lower mortality than CURB-6, and PSI-HR identified more high-risk patients with a non-significantly higher mortality than CURB-65. Prognostic performance was higher for PSI-HR than CURB-65 in the 3 lowest risk classes and was similar for both prediction rules in the 2 highest risk classes. PSI-HR had higher overall discriminatory power in predicting mortality than CURB-65. The prognostic performance of PSI-HR was superior to the PSI for high-risk patients and was marginally inferior to the PSI for low-risk patients.